Photosynthetic metabolism and antioxidant in Ormosia arborea are modulated by abscisic acid under water deficit? - S. S. Bastos; S. P. Q. Scalon; A. P. R. Souza; D. M. Dresch; F. S. Junglos; L. Q. Scalon; R. M. Mussury; V. M. B. Freitas (Brazilian Journal of Biology, 2021)
Abstract The aim of this research was to evaluate the effect of abscisic acid (ABA) on gas exchange and the activity of antioxidant enzymes of Ormosia arborea (Vell.) Harms seedlings under water deficit and its influence on the recovery potential of the seedlings. The experiment was conducted using four treatments, being daily irrigation or water restriction without and with 10 μM ABA. Seedlings under water deficit + ABA showed greater adjustment to drought, and when re-irrigated, they restored photosynthetic metabolism and water potential. ABA minimizes the reduction in the photosynthetic metabolism and water potential of the leaf, however, it does not increase the antioxidant activity of the O. arborea seedlings under water deficit. These results suggest that this species exhibits plasticity, which enables it to survive also in environments subjected to temporary water deficit regardless of the supplementation of ABA. We suggest that other doses of ABA be researched to expand the beneficial effect of ABA on this species.